Software defined radio for Schottky analysis in storage rings. (October 2020) - Dmytriiev, D.; Sanjari, M. S.; Litvinov, Yu. A.; Stöhlker, Th.
Abstract: Resonant Schottky cavity pickups have applications in the measurements of beam parameters in a storage ring. Apart from that they can be used in nondestructive in-ring decay studies of radioactive ion beams. In order to obtain the results of an experiment suitable Data Acquisition System (DAQ) is necessary. Several DAQs were used at Experimental Storage Ring (ESR) at GSI based on the different hardware and software solutions such as TCAP or NTCAP. The goal of this work is to design a prototype of a DAQ using open hardware and open source software defined radio (SDR) and conduct the test measurements at ESR.